EKSISTENSI KOMISI YUDISAL DALAM STRUKTUR KETATANEGARAAN REPUBLIK INDONESIA DAN YANG SEHARUSNYA DIATUR DALAM PERATURAN PERUNDANG-UNDANGAN - Fauzan, Muhammad (Faculty of Law, Universitas Jenderal Soedirman, 2008)
Existence of Judicial Commission in system of Republic of Indonesia is a long process in searching format of civic specially related to execution of judicial power. The chaos of execution of judicial power which influence of government and other power's have pushed the importance of a institute that able to